Effects of mindfulness training on perceived stress, self-compassion, and self-reflection of primary care physicians: a mixed-methods study - Herman van Wietmarschen (BJGP Open, 2018)
Background: Primary care physicians are subjected to a high workload, which can lead to stress and a high incidence of burnout. A mindfulness training course was developed and implemented for primary care physicians to better cope with stress and improve job functioning. Aim: To gain insight into the effects of the mindfulness training on perceived stress, self-compassion, and self-reflection of primary care physicians. Design & setting: A pragmatic mixed-methods pre–post design in which physicians received 8 weeks of mindfulness training. Method: Participants completed validated questionnaires on perceived stress (Perceived Stress Scale [PSS]), self-compassion (Self-Compassion Scale [SCS]), and self-reflection (Groningen Reflection Ability Scale [GRAS]) before the training, directly after, and 6 months later. Semi-structured interviews were conducted with six participants after the training and a content analysis was performed to gain in depth understanding of experiences. Results: A total of 54 physicians participated in the study. PSS was reduced (mean difference [MD] -4.5, P<0.001), SCS improved (MD = 0.5, P<0.001), and GRAS improved (MD = 3.3, P<0.001), directly after the 8-week training compared with before training. Six months later, PSS was still reduced (MD = -2.9, P = 0.025) and SCS improved (MD = 0.7, P<0.001). GRAS did not remain significant (MD = 2.5, P = 0.120). Qualitative analysis revealed four themes: being more aware of their own feelings and thoughts; being better able to accept situations; experiencing more peacefulness; and having more openness to the self and others. Conclusion: Mindfulness training might be an effective approach for improving stress resilience, self-compassion, and self-reflection in primary care physicians.